Perlindungan Hukum Bagi Konsumen Yang Melakukan Pinjaman Online Menurut Undang-Undang Nomor 8 Tahun 1999 Serta Pengawasan Terhadap Online Pinjaman Yang Belum Memiliki Izin - Yosef Anggit Yonatan; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2022)
Many kinds of innovations have developed due to technological advances, one of which is the servicesprovided by the company using the latest technology by facilitating consumer to get online-based lendingand borrowing services. The company provides a platform for easy access to borrow and borrow moneyin an easy and fast way and without collateral, but if the borrower (debtor) is late in paying the loan pastthe due date, interest will be charged, if it still does not pay the company (creditor) will order thecollector/debt collector to collect it, besides that many companies leak the borrower’s (debtor) personaldata that should be confidential. Therefore, through this research, it is to acquire the form of protectionthat is legal for consumers who make online loans and supervision of online loans that do not have apermit. Normative juridical is chosen for this research method with a case approach and legislation. Theresults of the study that the form of consumer insurance legal protection in this case is preventive andrepressive protection. Preventive prevention before the occurrence of a dispute, and repressively reportingto the Financial Services Authority Government Agencies. In this essential fact, the borrower can resolvethe problem through legal remedies, namely non-judicial (outside the court) and judicial (judicial) legalremedies.